The Effect of Kangaroo Mother Care on Neonatal Outcomes in Iranian Hospitals: A Review - Leila Sarparast; Roya Farhadi; Maryam Sarparast; Shabnam Shafai (Mazandaran University of Medical Sciences, 2015)
Context: Kangaroo Mother Care (KMC) is a supportive technique that beings at the neonatal period and is one of the skin-to-skin contact methods of holding neonate by mother. This method has an important role in exclusive breastfeeding and thermal care of neonates. This study aimed to investigate the application of KMC and evaluate the effect of this technique in different neonatal outcomes, particularly in Iranian neonates. Moreover, this review can be a tool for formative evaluation for this newly introduced treatment intervention in Iran. Evidence Acquisition: This review was conducted in national and international databases concerning experience with KMC on term and preterm neonates admitted in Iranian hospitals from 2006 to 2014. The measured outcomes included physiologic, psychologic, and clinical effects of this practice on newborn infants. Results: In this study, 42 Persian and English language papers were reviewed and finally 26 articles were selected. Various effects of KMC on different factors such as analgesia; physiological effects, breastfeeding, icterus, length of hospitalization, infection, psychologic effects, and weight gain were found. Conclusions: The results showed that as a simple and suitable strategy for increasing the health status of the mothers and newborns, KMC had an important role in improvement of neonatal outcomes in neonatal wards of Iranian hospitals in recent ten years. Therefore, promoting this technique in all neonatal wards of the country can promote health status of this population.